Analisis Faktor-Faktor Yang Mempengaruhi Tidak Optimalnya Kunjungan Antenatal Care Pada Ibu Hamil dengan Hipertensi Trimester III di RSUD Sultan Imanuddin Pangkalan Bun Kalimantan Tengah - Suharmi suharmi; Dumilah Ayuningtyas; Cicilya Candi (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2021)
Hypertension in pregnancy can cause death of mother and baby. According to the data for basic health research in 2018, there were 2,658 out of 80,544 people in hypertension during pregnancy among women aged 15-49. This study aims to reduce maternal and infant mortality by increasing antenatal care visits. Research methods: observational analytic with cross sectional test. Retrieval of data from the Medical Record from January to December 2019 at Sultan Imanuddin Hospital. The population used throughout the pregnant women with third trimester hypertension is taken out with a total sampling technique as many as 109 people, the excretion criteria of a pregnant women with normal blood pressure. Data were analyzed using chi-square test on version 23 of SPSS program. Statistical test results have the most sidnificant risk of a less suggestive antenatal care visit with hypertension being the pregnant women parity, having OR 0.004 p= 0.283 risky paritas having a tendency to lack antenatal care. The age og pregnant women OR 0.929 p= 0.145 means that she is at risk in life, with a tendency to develop a lack of antenatal care, of 1.929 or 1 times greater than that of a non-risk. Further gained a trust interval, bearing no ratio 1 value meaning there is a link between parity and the age of the pregnant women and poor antenatal care visit with a test of 5% significance. Conclucion management of pregnant women with hypertension where they have been diagnosed at least 4 times during pregnancy, if there are complication and high risk there is a policy of BPJS on the antenatal care every 2 weeks in trimester III as one of the prevention and control of maternal mortality and birth rates.